ChemInform Abstract: Enantiopure cis‐2, 5‐Disubstituted 2, 5‐Dihydropyrroles from D‐Glycal‐Derived Vinyl Aziridines. Issue 19 (13th May 2014) - Di Bussolo, Valeria; Frau, Ileana; Crotti, Stefano; Uccello‐Barretta, Gloria; Balzano, Federica; Pineschi, Mauro; Crotti, Paolo
Abstract The Li‐enolates of the methylene active compounds [(II) and (V)] react stereoselectively with the d‐glycal‐derived vinyl aziridines [(I) and (V)] to the title highly functionalized pyrrole derivatives in a unique manner.